Conferencia clínico-patológica (CPC) : trasplantado renal con nódulos pulmonares (2012)
ABSTRACT: We report the case of a 41 year-old man, who had a renal transplantation in 2005. He was admitted to the hospital because of 10 days of fever, diarrhea and respiratory symptoms. During his stay, a nodular lesion in the skin, several pulmonary nodules and colon ulcers were documented; due to his past medical history he was highly suspicious of having a fungal infection; antifungal therapy was started, but he died due to respiratory insufficiency.